AN EVALUATION OF THE SPEAKING ASSESSMENT TASKS USED BY AN ENGLISH TEACHER OF SMK NEGERI 4 MAKASSAR (A CASE STUDY) - Imran Trista Udin (Elite : English and Literature Journal, 2016)
The objectives of this research were to find out (1) The description of the validity of speaking assessment tasks used at SMK Negeri 4 Makassar (2). The description of the reliability of speaking assessment tasks used at SMK Negeri 4 Makassar. This research applied quantitative description. The population was the eleventh grade students of Tourism Department at SMK Negeri 4 Makassar in 2011/2012 academic year. The population consisted of 30 students where the sample was taken by using purposive sampling technique. The research data were collected by expert validation, concurrent validity, content validity, face validity, test retest, reliability and inter rater reliability on speaking assessment task and analyzed by using SPSS 17.0 version to see the significant difference between test retest, concurrent validity and inter rater reliability. Then, the data on the expert validation collected by using expert validation and content validity and face validity collected by using native speaker analysis and comment. The results of the research were: (1) The reliability of speaking assessment tasks used at SMK Negeri 4 Makassar is high reliable and (2) the validity of speaking assessment tasks used at SMK Negeri 4 Makassar is valid. The researcher concluded that teaching material especially in speaking tasks is valid and reliable to teach at SMK (vocational school) where the English language teaching process is demanded to teach communicatively and functionally, so the SMK’s students possess English competencies which are relevant to the Job opportunities both in Indonesia and global setting.